Colaboração e cognição na World Wide Web - Pascoal, Roger (2008)
The collaboration is present in sites that appeared in the last times and become widely used, such as Flickr and YouTube. And, if on the one hand it represents the same ideals intended by the inventors of the World Wide Web, on the other hand it is a reinvented process in accordance with the new available technological possibilities at the current moment. Thus, this research seeks to deepen the understanding about collaboration and how it had developed in the net. It intends to understand the features of collaborative production in cyberspace and to verify the existence of an emergent knowledge from it. The research is divided in five parts. In the first one, the Web development highlighting its collaboration features. In the second, the formation of cyberspace through telematics. In the third, the human cognition in accordance with perspective of the complexity theories and knowledge biology. In the fourth, cognitives technologies and the reflections about coletive cognition. In the fifth, in relation with the previous subjects, the observation of collaborative potential of web architectures and how they can contribute to the knowledge production